PAN-ISLAMISM AND THE JIHAD DISCOURSE OF THE GERMAN ORIENTALISTS IN THE FIRST WORLD WAR - Avcı, Remzi (Journal of Al-Tamaddun, 2019)
Pan-Islamism and jihad became very popular topics in Germany before and during the First World War, in particular among journalists, politicians, diplomats and orientalists. After the declaration of Ottoman jihad against the Entente powers in 1914, some German orientalists in particular felt that it was their responsibility to write about jihad and pan-Islamism. This article first examines the approaches of the German academic orientalists to German Orient policy, pan-Islamism and jihad, by analyzing the similarities and contrasts between the texts of the orientalists as part of a network. It then tries to determine the role of the German academic orientalists in shaping German strategy towards Islam in the First World War. Although the focus is on texts written between 1914 and 1916, some works of orientalists written before the First World War are also considered, in order to understand how their thoughts changed over time.